Kebijakan Eropa terhadap Pendanaan, Kurikulum, dan Guru Sekolah Islam: (Studi Komparatif di Belanda, Inggris, Jerman, Prancis, dan Swedia) - Nur Kholis; Tatag Satria Praja (UIN Sunan Ampel Surabaya, 2019)
This study aims to reveal the policies of European countries, such as the Netherlands, Britain, Germany, France and Sweden, towards Islamic schools. The focus of the study includes three interrelated themes, namely policies on education funding, Islamic Religious Education (IRE) curriculum, and empowerment of IRE teachers. Data from relevant literature were collected and analyzed using an analytical-comparative approach. The main findings of this study are as follows. First, with regard to funding, the Netherlands and Sweden fund all Islamic schools; Britain and France only fund Islamic schools that follow national education regulations; and Germany funds only IRE teacher salaries. Second, for the curriculum policy, Germany and the UK include IRE in public schools; The Netherlands and Sweden leave the IRE curriculum to each Islamic school; while France integrates IRE into other subjects in public schools. Third, with regard to teachers, the Netherlands requires IRE teachers to undertake certified teacher training at universities; England and Sweden require that they take postgraduate-level education courses; France requires that they take courses containing religious topics; and Germany requires them to take Islamic theology courses.